Extraction and analysis of safranal and crocin in pure saffron (crocus sativus) - Emma, Suali (2006)
A number of methods for the preparation, extraction and HPLC analysis of saffron were evaluated to determine a reliable method for quantifying safranal and crocin in Crocus sativus L. stigma tissues. Samples of saffron from Kashmir India have been chosen to use in this experiment. A simple, sensitive and specific High Performance Liquid Chromatography has been chosen to be analyzing the safranal and crocin in stigma of saffron. There are four different methods that have been used in this experiment. In method l,sample were extracted by acetonitrile and water, in method 2,sample were extracted by ethanol and water, in method 3,sample were extracted acetonitrile and water but vaporized using rotary evaporator unit and in method 4,the sample have been extracted by ethanol and water followed evaporation by rotary evaporator unit. Preparation methods such as heating stigmas at 80°C for 30 min prior to extraction and followed by immediate HPLC analysis increased the concentration of safranal and crocin several fold compared to stigmas which had been prepared by freeze drying. Other equipments that have been used in this experiment are microcentrifuger to centrifuge the sample, water bath and oven to increase the level of saturation. Using different solvent to extract the stigma of saffron also effect the level of chemical composition in each sample.Safranal reacted more to acetonitrile compare to ethanol and crocin reacted more to ethanol compare to acetonitrile. The purpose of preparation of ethanol and water or acetonitrile stigma extracts by drying with a rotary evaporator prior to HPLC analysis were to find the effect of temperature to the stigma of saffron in which the boiling point of crocin is more 186 °C,safranal is 70°C, ethanol is 78.4 °c and acetonitrile is 82°C.